2021
DOI: 10.1016/j.jviromet.2020.114031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of potency assays to assess SARS-CoV-2 neutralizing antibody capacity in COVID-19 convalescent plasma

Abstract: Highlights Transfusion of sera of convalescent patients is currently in clinical evaluations to treat COVID-19 patients. The level of neutralizing antibodies vary among convalescent patients and fast and simple methods to identify suitable plasma donations are needed. We compared three methods to determine the SARS-CoV-2 neutralizing activity of human convalescent plasma. An ELISA-based sVNT assay required the lowest biosafety level, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 24 publications
5
85
0
Order By: Relevance
“…Twelve of 43 SARS-CoV-2-positive individuals presenting no or weak neutralizing titers agrees with a study of COVID-19 recovered patients (33).…”
Section: Seroneutralization Assaysupporting
confidence: 83%
See 2 more Smart Citations
“…Twelve of 43 SARS-CoV-2-positive individuals presenting no or weak neutralizing titers agrees with a study of COVID-19 recovered patients (33).…”
Section: Seroneutralization Assaysupporting
confidence: 83%
“…A recent work reported that standard commercially available SARS-CoV-2 IgG results could be a useful surrogate for neutralizing antibody testing (32). However, in the present study, antibody neutralizing titers were determined in vitro by using a native SARS-CoV-2 strain to be closer to the physiological infection of cells by SARS-CoV-2 in northeast France (33). Twelve of 43 SARS-CoV-2–positive individuals presenting no or weak neutralizing titers agrees with a study of COVID-19 recovered patients (33).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When using the manufacturer’s cut-off for a positive result (≥20%), we find in all 3 groups that more than 90% of donors show a positive result. If the cut-off according to Rein et al [ 18 ] is adjusted, it can be seen that in group 1 only 30%, in group 2 78% and in group 3 still 96% of the donors are positive ( S4 Fig ). Based on this result, a correlation was calculated which showed a rho of 0.720 and a p.value of <0.001.…”
Section: Resultsmentioning
confidence: 99%
“…Mazzini et al [ 153 ] observed that the RBD-based ELISA was efficient for quantifying IgA, IgM and IgG neutralizing antibodies against SARS-CoV-2. However, the study by von Rhein et al [ 154 ] showed that although the ELISA is capable of quantifying neutralizing antibodies, its performance was lower when compared to the plate reduction neutralization test (PRNT) and a lentiviral vector based pseudotype neutralization assay. The low performance of this assay in this context may be related to its ability to detect only neutralizing antibodies that block the interaction between the RBD region and the receptor-angiotensin converting enzyme II (ACE2) and, even though most neutralizing antibodies have this action, other types of neutralization mechanisms have been described [ 155 ].…”
Section: Serological Testsmentioning
confidence: 99%